Hong Kong linked exchange rate system - Hong Kong Monetary Authority (Hong Kong : Hong Kong Monetary Authority, 2000)
This book is to contribute to general knowledge about the link (The Hong Kong's linked exchange rate system has the Hong Kong dollar linked to the US dollar at the fixed rate of HK$7.8 to one US dollar) by offering factual information about its origins and operation, and some comment on its benefits and drawbacks.
gau 18/10/2016
Ref
Keywords: Exchange rate; Monetary Policy; Currency Question; Hong Kong